Analysis of the Effect of Electrode Variation and Current on the Welding Results of Corten A Steel using SMAW Method on Microstructure, Corrosion Resistance, and Mechanical Properties - Mavindra Ramadhani; Rochman Rochiem; Muhammad Irsyad Zain (Journal of Applied Sciences, Management and Engineering Technology, 2023)
The emission exhaust stack in industries must have good corrosion resistance and heat resistance in both the base metal and the welded joints. Therefore, corten steel is chosen as the base metal for the exhaust stack due to its excellent corrosion resistance and heat resistance, as well as its costeffectiveness compared to other heat-resistant steels. This study aims to analyze the welded joints of corten steel in terms of microstructure, corrosion resistance, and tensile strength using the Shielded Metal Arc Welding (SMAW) method, following the Welding Procedure Specification (WPS). The variables used in this study are the electrode variations using E7016-G and E8016-G electrodes, and the current variations of 90, 105, and 120 A. The results of this study indicate that in the metallography testing, the highest percentage of the perlitic phase is found in specimen B2, which uses the E8016-G electrode and a current of 105A, reaching 41.92% in the weld metal and 29.6% in the Heat-Affected Zone (HAZ). In the corrosion resistance testing, the corrosion rate fluctuates within the 3-hour and 6-hour time ranges, but decreases within the 10-hour time range. The lowest corrosion rate is observed in specimen B2 using the E8016-G electrode and a current of 105A. In terms of mechanical properties, the best results are obtained from the tensile testing and hardness testing of specimen B2 using the E8016-G electrode and a current of 105A.